E-commerce during COVID - Alcedo, Joel,Cavallo, Alberto,Dwyer, Bricklin,Mishra, Prachi,Spilimbergo, Antonio (International Monetary Fund, 2022)
We study e-commerce across 47 economies and 26 industries during the COVID-19 pandemic using aggregated and anonymized transaction-level data from Mastercard, scaled to represent total consumer spending. The share of online transactions in total consumption increased more in economies with higher pre-pandemic e-commerce shares, exacerbating the digital divide across economies. Overall, the latest data suggest that these spikes in online spending shares are dissipating at the aggregate level, though there is variation across industries. In particular, the share of online spending in professional services and recreation has fallen below its pre-pandemic trend, but we observe a longer-lasting shift to digital in retail and restaurants
10.5089/9781616359218.001
Keywords: Graue Literatur; digitalization; e-commerce; Intellectual Property Rights; International Economics; Macroeconomics and Monetary Economics; Technological Change; COVID-19; consumption; Innovation; Research and Development; Industries: Hospital; Travel and Tourism; Money and Monetary Policy; Public Finance; Economics: General; Intellectual Property Rights: General; Macroeconomics and Monetary Economics: General; International Economics: General; Health Behavior; Monetary Policy; Central Banking; and the Supply of Money and Credit: General; National Government Expenditures and Related Policies: General; Macroeconomics: Consumption; Saving; Wealth; Sports; Gambling; Restaurants; Recreation; Economic & financial crises & disasters; Economics of specific sectors; Infectious & contagious diseases; Monetary economics; Public finance & taxation; Hospitality; leisure & tourism industries; Macroeconomics; Health; Money; Expenditure; Diseases: Contagious; National accounts; Economic sectors; Currency crises; Informal sector; Economics; Communicable diseases; Consumer credit; Expenditures; Public; Consumption; Economics; Tourism